Integrative description of Mesobiotus anastasiae sp. nov. (Eutardigrada, Macrobiotoidea) and first record of Lobohalacarus (Chelicerata, Trombidiformes) from the Republic of South Africa - Tumanov, Denis V. (European Journal of Taxonomy, 2020)
A new species of the genus Mesobiotus is described from the Republic of South Africa using a traditional morphological approach (light and scanning electron microscopy) combined with molecular analysis (18S rRNA, 28S rRNA, ITS-2 and COI markers). Mesobiotus anastasiae sp. nov. differs from all known Mesobiotus species by having a unique combination of characters of the adult animals and the eggs. Adults of the new species have an oral cavity armature without elongate teeth in the second band, while the processes of the egg chorion have a basal collar and distinct rows of large pores. An updated key to the species of the genus Mesobiotus, including 66 of 70 currently described species, is given. An aquatic mite species from the Lobohalacarus weberi complex (freshwater Halacaridae) co-occurs with M. anastasiae sp. nov., suggesting that the newly described tardigrade inhabits constantly wet moss cushion habitats.